Doing business in the Middle East and gender issues on the example of Saudi Arabia and the United Arab Emirates - Belova, Valeriia; Semenenko, Vadim; Chvátalová, Kateřina; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
This paper is dedicated to European businesses that want to cooperate with the United Arab Emirates and the Kingdom of Saudi Arabia in any way or expand European business to these countries. The main goal of this work is to give them recommendations, which will be based on evaluating the current situation in the United Arab Emirates and the Kingdom of Saudi Arabia in a matter of doing business and the role of gender in it. The position, scope of work, and responsibilities a woman can take in these countries, considering the execution of strict norms of Islam, will be assessed. The United Arab Emirates and the Kingdom of Saudi Arabia are both countries located on the Arabian Peninsula; they border with each other. Yet, these countries’ approaches towards gender and the speed of progress in equality and diversity in business are very different. That is why these two countries were chosen to be compared with each other. These states are very fast developing, and their role and importance in the international market have only been growing. Hence, cooperation with them is inevitable. So, the extent to which women are constrained in their opportunities and rights in doing business will be estimated, and the actions of these states regarding the improvement and promotion of parity will be taken into consideration.
Vedoucí práce: Vadim Semenenko
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses